Understanding Of Taxation, Tax Socialization, Tax Sanction, And Tax Rate Towards Taxpayer Compliance Of Micro, Small And Medium Enterprises (Survey Micro, Small And Medium Enterprises In Surakarta) - Cahya Erie Sulistyaningsih; Cahyani Tunggal Sari (Journal of Indonesian Science Economic Research, 2019)
This study aims to determine the effect of understanding taxation, tax socialization, tax sanction, and tax rate towards taxpayer compliance of micro, small and medium enterprises. This Study population is a micro, small and medium business taxpayer in Surakarta. The method of data collection uses primary data with a questionnaire. Result of analysis indicate that all valid proven questionnaire and reliabel. Result of assumption test classical indicate that data in this research is proven is normal distribution, free from the existence of heterokedastisitas, multikolonieritas and autokorelasi. Result of regresi test with t test indicate that variable understanding of taxation, tax socialization, tax sanction, and tax rate have an effect on by partial towards taxpayer compliance of micro, small and medium enterprises while according to test indicate that understanding of taxation, tax socialization, tax sanction, and tax rate have an effect on by simultan towards taxpayer compliance of micro, small and medium enterprises.